PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN SUKOHARJO DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Sundari Sundari; Antin Okfitasari (Jurnal Akuntansi dan Pajak, 2017)
The purpose of this study was to test the significance of the influence of communication, work environment on employee performance Regional Planning Agency Sukoharjo with motivation as an intervening variable. The population in this study were employees of the Regional Development Planning Agency Sukoharjo. The sample in this study all employees. Data used in the study is primary data taken with a list of statements given to all employees. The analysis tools used are validity , reliability testing, linearity test, path analysis, t test, F test, test and correlation coefficient of determination. Individual testing of the hypothesis showed that communication variables, working environment and significant positive effect on employee motivation. Variable communication, working environment and motivation positive and significant impact on employee performance. Together - each variable communication, working environment and motivation positive and significant impact on the performance variables. Direct influence on the performance of communication larger than the indirect effect of communication on performance through motivation. Motivation in mediating the relationship between communication with ineffective performance. Direct influence on the performance of the work environment is greater than the indirect effect of work environment on performance through motivation. Motivation in mediating the relationship between work environment with ineffective performance. Because motivation is not effective in mediating the relationship between communication and performance of the work environment with motivation serve as independent variables.Keywords :communication, work environment, motivation, performance